Pengaruh Kualitas Jasa Pelayanan di Masa Pandemi Covid-19 terhadap Kepuasan Pengguna Jasa di PT. Pelabuhan Indonesia II (Persero) Cabang Panjang Bandar Lampung - Suryani Suryani; Suradi; Mohamad Syahroni (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2022)
The purpose of this study was to analyze the effect of service quality during the Covid-19 pandemic at PT. Pelabuhan Indonesia II (Persero) Panjang Branch. This company is a State-Owned Enterprise (BUMN) which is engaged in port services that provides port facilities and infrastructure in order to support the smooth flow of ships. This research type is an associative research that aims to analyze the influence of one variable with another variable. This study uses descriptive analysis techniques and multiple linear regression analysis. The population in this study were customers of PT. Pelabuhan Indonesia II (Persero) Panjang Branch in Bandar Lampung in 2021 as many as 380 customers. The sampling method used random sampling with a total sample of 80 respondents. Primary data was collected through the distribution of questionnaires. The results showed that simultaneously service quality had a positive and significant effect on customer satisfaction. The value of the coefficient of determination can be seen from the Adjusted R Square of 0.577 which means that 58.87% of the customer satisfaction variable can be explained by the quality of service. While the other 42.13% difference is influenced by government regulations which are not included in this study. Keywords: service quality, customer satisfaction